GENDER DI MASA KRISIS: TELAAH REFLEKSI KEPEMIMPINAN PEREMPUAN DAN DAMPAK PANDEMI COVID-19 TERHADAP PEREMPUAN - Asep Kurniawan (IAIN Syekh Nurjati Cirebon, 2021)
The purpose of this study was to reveal in depth the leadership of women during the Covid-19 pandemic and the impact of the Covid-19 pandemic on her. This research used a qualitative method with normative law which was carried out by reviewing the literature. The approach used a contextual and statutory approach. The data were organized, analyzed inductively, and classified into many units and formulated into a pattern. The results showed that the progress of female leaders during Covid-19 was quite successful in controlling the condition with their leadership strengths. However, in general, this Covid-19 pandemic negatively impact on the lives of almost the entire population of the world, especially for women, namely, the multiple burdens of child care and work, the threat of domestic violence, and unequal treatment in the economic sector. All of these impacts showed that the Covid-19 pandemic was not gender-neutral due to the position of women who positioned unbalanced from the beginning with men in the economic and social sectors. For this reason, there should be emancipation efforts to initiate policies that were sensitive to gender issues in overcoming the Covid-19 pandemic.